INVESTIGAŢIILE ARHEOLOGICE LA SITUL SAHARNA MARE / „DEALUL MĂNĂSTIRII”, RAIONUL REZINA (2017-2019)* - Niculiţă, Ion; Zanoci, Aurel; Băţ, Mihail; Dulgher, Victor (My University, 2019)
The archaeological research conducted in 2017-2019 was concentrated in the southwest part of the site, where as a result of the geomagnetic measurements a positive anomaly was attested that denotes the presence of burned structures. Following the archaeological excavations (256 m2) in this part of the settlement, three layers of living were identified: Holercani-Hansca, Cozia-Saharna and Thracian-Getae. It was discovered a pit (7/2018) belonging to the Holercani-Hansca horizon whose filling contained ceramics characteristic of this culture. For the Cozia-Saharna layer was found a structure (4/2017-2019), 12 pits, a burial, and various archaeological inventory represented by work tools, weapons and ceramics ornamented with incised and stamped ornaments. In the Thracian-Getae layer were uncovered three structures, 13 pits and a rich archaeological findings. Among the inventory items are tools and utensils made of different raw materials – iron, bronze, bone and horn, stone and burnt clay. From this layer come several weapons, in particular, tips of bronze arrows, as well as pieces of jewelry, represented by fibuale, bracelets, rings etc. Also, from the Thracian-Getae layer was recovered a significant amount of local ceramics and Greek imports

Археологические исследования 2017-2019 годов были сосредоточены в юго-западной части памятника, где в результате геомагнитных разведок была обнаружена положительная аномалия, свидетельствующая о наличии сгоревших строительных сооружений. Археологические исследования (256 м2) в этой части поселения показали наличие трех культурных слоев: Холеркань-Ханска, Козия-Сахарна и фрако-гетского. Так, к горизонту Холеркань-Ханска относится яма (7/2018), в заполнении которой находилась керамика, характерная для этой культуры. К слою Козия-Сахарна относится постройка (4/2017-2019), 12 ям, захоронение, а также разнообразный археологический инвентарь, представленный орудиями труда, оружием и керамикой с резным и штампованным орнаментом. Фрако-гетский культурный слой включает: три постройки, 13 ям и богатый археологический инвентарь. Среди находок – орудия труда, изготовленные из разного сырья – железа, бронзы, кости и рога, камня и обожженной глины. Также в этом слое обнаружены предметы оружия, в частности бронзовые наконечники стрел, а также украшения, представленные фибулами, браслетами, кольцами и т. д. Кроме того, в фрако-гетском слое было найдено значительное количество местной керамики, а также греческой импортной.
Археологические исследования на памятнике Сахарна Маре / «Дялул Мэнэстирий», Резинский район (2017-2019)
Archaeological investigations at the Saharna Mare site / „Dealul Mănăstirii”, Rezina district (2017-2019)
Keywords: regiunea Nistrului Mijlociu; epoca fierului; Middle Dniester region; Iron Age; Среднее Поднестровье; железный век